MODEL MATEMATIKA PENYEBARAN FLU BURUNG DENGAN TREATMENT PADA MANUSIA DAN DINAMIKA POPULASI RECRUITMENT-DEATH PADA UNGGAS - Afifah, Dewi Aulia; Kharis, Muhammad; Noor Asih, Tri Sri (Universitas Negeri Semarang, 2019)
Avian influenza is ​​a disease caused by H5N1 virus type A. The spreading process of avian influenza caused by wild poultry migration. Avian influenza is transmitted from poultry to poultry and from poultry to humans through saliva, mucus of nose and feces. The disease can cause death for humans with high mortality. Deaths due to infection avian influenza virus can be avoided by giving treatment for humans and burning infected poultry. Therefore, considering how dangerous avian influenza disease for humans, it is very necessary for humans to study this disease, one of them with a mathematical model of avian influenza. We analyzed the existence of the equilibrium point of the model and its stability analysis of the equilibrium point. The simulation gives results to validate the interpretation of analytic and numerical results from the analysis process.